2013
DOI: 10.5194/npg-20-293-2013
|View full text |Cite
|
Sign up to set email alerts
|

On the role of electromagnetic phenomena in some atmospheric processes

Abstract: A crucial part of electromagnetic phenomena in many atmospheric processes is verified by systematized data. The multilayered charged system of clouds represents some dynamically equilibrium structure kept by the ionic and polarization forces. The estimates of acting forces are presented and the necessity of taking into account the plasma-like subsystems' effect on some atmospheric phenomena is demonstrated, including the formation and the maintenance of the structure and characteristics of their movement

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
6
0
2
Order By: Relevance
“…The electromagnetic phenomena play a significant role in many of the atmospheric processes. Electromagnetic forces could influence both generation (and maintenance) of the charged structure and the motion of tropical cyclones [29]. In reference [30], it is reported that the electrostatic forces could contribute to the warming of climate by increasing the concentration of large particles in atmospheric dust.…”
Section: Effects Of the Electric Field On The Electrical Properties Omentioning
confidence: 99%
“…The electromagnetic phenomena play a significant role in many of the atmospheric processes. Electromagnetic forces could influence both generation (and maintenance) of the charged structure and the motion of tropical cyclones [29]. In reference [30], it is reported that the electrostatic forces could contribute to the warming of climate by increasing the concentration of large particles in atmospheric dust.…”
Section: Effects Of the Electric Field On The Electrical Properties Omentioning
confidence: 99%
“…Все виды ионизации аэрозолей мы рассматриваем в качестве климатического влияния. В динамике аэрозольных подсистем заметное влияние имеют электрические поля, усиливающие атмосферную вихревую активность [7][8][9]. При фазовых переходах влаги, инициируемых заряженными аэрозолями, генерируются плазменные вихри, а неравномерный нагрев подобных мозаичных структур влияет и на образование крупномасштабных атмосферных вихрей.…”
Section: бисерные молнии как стохастические структуры электростатичесunclassified
“…Connected with them plasma vortices can influence on the development of vortex formations in the Earth's atmosphere (Artekha, Belyan 2013;Izhovkina et al 2016;Sinkevich et al 2017).…”
Section: The Effect Of Electrostatic Perturbations On the Activity Of Plasma Vortices And The Structure Of Lightningmentioning
confidence: 99%